Growth and economic impact of Boer type goats fed diets with corn gluten feed and cor dried distillers grain with solubles as a substitute for soybean meal - Headrick, Emily E.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
Corn co-products are a relatively inexpensive protein source when compared to soybean meal (SBM) and is readily available in the Midwest. This experiment was conducted to determine the growth and economic impact of replacing SBM with varying levels of corn dried distillers grain with solubles (DDGS) and corn gluten feed (CGF) in Boer-type goat growth performance. The experiment was 35 d and included 75 Boer-type goats (26 ± 0.2kg, approximately 70 d of age). Goats were divided into 3 goats per pen and 5 pens per treatment with diets being randomly assigned to each pen, with the pen as the experimental unit. The diets were isocaloric and isonitrogenous diets, but varied in protein sources, 1)100% SBM; 2)100% DDGS/0% CGF; 3)66% DDGS/33% CGF, 4)33% DDGS/66% CGF; 5)100% CGF/0% DDGS. Data was collected by recording how much feed was added on a daily basis and weighing goats and feeders once a week. The GLIMMIX procedure of SAS (v. 9.4, Cary, NC) was used to analyze the data with an alpha value equal to 0.05. No difference in final BW, ADG, ADFI, and G:F was detected (P>0.05) with changing protein source. Replacing SBM with corn co-products lowered feed cost/ kg of feed about $0.04 but there was no detected evidence (P>0.05) that replacing SBM affected cost/kg of gain. However, feed cost/goat was significantly lower (P=0.0008) when SBM was replaced by corn co-products. In conclusion, CGF and DDGS can economically replace SBM in Boer-type goat growing diets.
Keywords: Spring 2019